Neurologic dysfunction and genotoxicity induced by low levels of chlorpyrifos - Muller, Mariel (2014)
Chlorpyrifos (CPF) is an organophosphorus cholinesterase inhibitor widely used as an insecticide. Neuro and genotoxicity of this agent were evaluated following daily subcutaneous injections at 0.1, 1 and 10 mg/kg or its vehicle to laboratory rats during one week, at the end of which somatosensory evoked potentials (SEP) and power spectrum of the electroencephalogram (EEGp) were recorded under urethane anesthesia. In another group of conscious animals, auditory startle reflex (ASR) was evaluated followed, after euthanasia, with measurements of plasma B-esterases, and genotoxicity with the alkaline comet assay (ACA) at the same CPF doses. The results indicated a CPF dose related inhibition of B-esterases. Enhanced inhibition of the ASR by a subthreshold pre-pulse was observed at all doses and ACA showed a significant higher DNA damage than vehicle controls in animals exposed to 10 mg/kg CPF. A trend to higher frequencies of EEGp and an increase in amplitude of the first negative wave of the SEP were found at all doses. The first positive wave of the SEP decreased at the CPF dose of 10 mg/kg. In summary, a shift to higher EEG frequencies and alterations of somatosensory and auditory input to the central nervous system were sensitive manifestations of CPF toxicity, associated with depression of B-esterases. The changes in electrical activity of the cerebral cortex and DNA damage observed at doses that do not elicit overt toxicity may be useful in the detection of CPF exposure before clinical signs appear.